(untitled) (Veterinary Science, 2020)
Polygonum hydropiperoides (swamp smartweed) is a perennial plant of the Polygonaceae family. The species of the genus Polygonum are cultivated and marketed for medicinal purposes, and in the rural area, they are used in animals as a healing. The action of the extracts of their aerial parts was analyzed on cellular and tissue components in incision wounds caused in mice. The lesions caused were treated topically for ten days with diluted extracts of the named species, obtaining daily samples to perform histological studies. At the same time, and to be able to compare the evolution of the wounds, a similar procedure was performed with mice that were not treated. Significant differences were observed in the arrival and presence of neutrophils and in the appearance of fibroblasts (Student t-test for two independent samples). Among other tissue changes, the increase in vascularity was also highlighted.